Quadricuspid aortic valve with complete heart block: a double whammy - Mukesh Dhillon; Aditi Sharma (The Egyptian Heart Journal, 2024)
Abstract Background Developmental abnormalities of aortic valve cusps are relatively common with the bicuspid valve being the most frequently encountered congenital heart disease. However, the quadricuspid aortic valve (QAV) is an exceedingly rare abnormality. Case presentation We report a case involving a young, otherwise healthy male who presented with non-exertional syncope and was subsequently diagnosed with complete heart block (CHB). Further evaluation revealed the coexistence of a rare quadricuspid aortic valve and CHB. This combination, in the absence of surgery or infective endocarditis, has only been reported once before in the literature.The patient underwent successful permanent pacemaker implantation and continues to be monitored for aortic regurgitation. Conclusions The coexistence of a QAV with CHB, in the absence of infective endocarditis or aortic valve surgery, is extremely rare and necessitates careful evaluation and follow-up.